Respiratory manifestations in the Ehlers–Danlos syndromes. Issue 4 (22nd November 2021) - Bascom, Rebecca; Dhingra, Radha; Francomano, Clair A.
Abstract: Persons with the Ehlers–Danlos syndromes (EDS) report a wide range of respiratory symptoms, most commonly shortness of breath, exercise limitation, and cough. Also reported are noisy breathing attributed to asthma, difficulty with deep inhalation, and inspiratory thoracic pain. The literature consists of case reports and small cross‐sectional and cohort studies. One case–control study estimated twofold to threefold greater respiratory disease burden among persons with EDS as compared to controls. The differential diagnosis for symptoms is broad. Structural alterations include pectus deformities, scoliosis, recurrent rib subluxations, and tracheobronchomalacia, associated with varying degrees of physiologic impairment. Those with vascular EDS have an increased risk of pneumothorax, intrapulmonary bleeding, cysts, and nonmalignant fibrous nodules. Functional aerodigestive manifestations such as inducible laryngeal obstruction may be misdiagnosed as asthma, with gastro‐esophageal dysmotility and reflux as common contributing factors. Inflammatory manifestations include costochondritis, bronchiectasis, and localized respiratory allergic and nonallergic mast cell activation. Cranio‐cervical instability can dysregulate respiratory control pathways. There is a need for careful phenotyping using standardized clinical tools and patient‐reported outcomes and continuing collaboration with aerodigestive specialists including otolaryngologists and gastroenterologists. Also needed is further evaluation of respiratory symptoms in persons with hypermobility spectrum disorders. Personalized monitoring strategies are invaluable for interpretation and long‐term management of respiratory symptoms.